Field notes contributed by Charles Fuller, fall 1991 - Fuller, Charleset al (1991)
List of birds and locations contributed by Charles Fuller. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1991. This item is related to a request for additional information on https://avian.lib.iastate.edu/documents/4722/view and related to field report https://avian.lib.iastate.edu/documents/4723/view. Epson - sheet feed